Critical success factors of supply chain integration for the maritime industry - Yuen, Kum Fai. (2012)
Supply Chain Integration (SCI) is defined as the adoption and use of collaborative and coordinating structures, processes, technologies and practices among supply chain partners for building and maintaining a seamless conduit for the precise and timely flow of information and materials. The current framework and critical success factor studies relating to SCI in the maritime industry are deficient. The objectives of this research are to (1) measure the degree of internal and external integration in the maritime supply chain, (2) investigate the causal relationship of the following critical success factors (i.e. organization commitment, strategic alignment, effective relationship management, integrated information technology, and standardized performance metric) on SCI and performances ,and (3) validate the relevant inhibiting and enabling factors for the above mentioned critical success factors. Both qualitative and quantitative methods were employed in this research. For qualitative, face to face interviews were conducted on individuals from shipping lines, port operators, third party logistics provider, and shippers. The purpose was to test for the feasibility of the framework in measuring SCI, and the critical success factors which were proposed in this study. Thereafter, analysis drawing on various statistical methods was conducted to extract meaningful results from the 142 completed surveys. The findings from this research show that integration in the maritime supply chain was more internal than external. This was primarily attributed by the weak attempt in coordination between maritime partners and also, incompatible information system that was noted to be deficient in both internal and external integration. Each of the critical success factors was hypothesized to have a positive influence on supply chain integration and supply chain performances. The results from hypothesis testing were significant except for standardized performance metric. Top barriers relating to SCI were found to be relational in nature which reflects the low score for coordination. This paper has attempted to consolidate the piecemeal studies on measuring SCI and has supplemented the lack of success-factors studies on the maritime industry. The framework in this research could serve as a reference for maritime firms to identify and act on their performance gaps, using the proposed solutions in this study. Future research work should focus on the causal relationship between supply chain power and integration which was found to be contradicting during the course of this research.